2011
DOI: 10.1038/nmat3078
|View full text |Cite
|
Sign up to set email alerts
|

Nucleation mechanism for the direct graphite-to-diamond phase transition

Abstract: Graphite and diamond have comparable free energies, yet forming diamond from graphite is far from easy. In the absence of a catalyst, pressures that are significantly higher than the equilibrium coexistence pressures are required to induce the graphite-to-diamond transition [1][2][3][4][5][6][7] . Furthermore, the formation of the metastable hexagonal polymorph of diamond instead of the more stable cubic diamond is favored at lower temperatures 2,5-7 . The concerted mechanism suggested in previous theoretical … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
242
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 323 publications
(269 citation statements)
references
References 32 publications
(62 reference statements)
13
242
3
Order By: Relevance
“…The two systems eventually begin to interact, and the graphene transitions to a layer of graphite. Interestingly, if pressure were applied still further, a second transition would occur from graphite to diamond, 37 as has been recently verified experimentally using femtosecond laser pulses to achieve the change. 38 However, what makes the graphene to graphite transition special is that it is the only known system where one can observe with atomic resolution how the electron acquires mass; or alternatively, how the electron loses mass and graphene generates the giant charge density responsible for its high current carrying capacity and thermal conductivity.…”
Section: E Vertical Displacement Total Energy Considerationsmentioning
confidence: 69%
“…The two systems eventually begin to interact, and the graphene transitions to a layer of graphite. Interestingly, if pressure were applied still further, a second transition would occur from graphite to diamond, 37 as has been recently verified experimentally using femtosecond laser pulses to achieve the change. 38 However, what makes the graphene to graphite transition special is that it is the only known system where one can observe with atomic resolution how the electron acquires mass; or alternatively, how the electron loses mass and graphene generates the giant charge density responsible for its high current carrying capacity and thermal conductivity.…”
Section: E Vertical Displacement Total Energy Considerationsmentioning
confidence: 69%
“…Observations and theoretical studies suggested a structural relationship among graphite, cubic diamond and lonsdaleite and an important role of the latter during the graphite-todiamond transition 3,[9][10][11][12][13][14] . Furthermore, an area centred around 18 GPa and 1,400 K in the pressure-temperature diagram for carbon was attributed to a phase called 'retrievable hexagonaltype diamond' 10 , which corresponds to the conditions where lonsdaleite has been reported 3,11,15 .…”
mentioning
confidence: 99%
“…Solid-solid transitions usually occur in a martensitic fashion [17,18] involving the concerted, diffusionless motion of the atoms in the unit cell. Anisotropic stress, rapid quenching, and a small system size have been found to promote martensitic transformations [19]. In colloids, martensitic transitions have been observed in small crystalline clusters [20][21][22] or lattices stretched by external fields [18,[23][24][25].…”
mentioning
confidence: 99%